Vietnam`s meat import market under Impacts of the European -Vietnam Free Trade Agreement and quality management demand - Minh Nguyen Doan; Viet Nga Le Thi; Huy Dinh Tran Ngoc (Zielona Góra: Faculty of Economics and Management Press)
The impact of Free Trade Agreement (FTA) on commercial business of the member could be assessed by the potential and tangible effects. This paper is adopted by Partial equilibrium theory and SMART tool to measure the impact of EVFTA on the Vietnamese meat import (HS code 02).
Keywords: EVFTA; Vietnam; UE; meat import; SMART; FTA; quality management; Wietnam; import mięsa; zarządzanie jakością